FNDC3B circular RNA promotes the migration and invasion of gastric cancer cells via the regulation of E‐cadherin and CD44 expression. Issue 11 (8th April 2019) - Hong, Yuling; Qin, Haifeng; Li, Yin; Zhang, Yuhai; Zhuang, Xunrong; Liu, Lei; Lu, Kun; Li, Long; Deng, Xiaoling; Liu, Fan; Shi, Songlin; Liu, Guoyan
Abstract: Circular RNAs (circRNAs) are a new class of RNAs, and many studies have identified thousands of circRNAs in tumor cells. Fibronectin type III domain‐containing protein 3B ( FNDC3B ) circular RNA (circFNDC3B, circBase ID: hsa_circ_0006156) circularizes with exons 5 and 6. Gibson Assembly DNA technology was used to construct a circFNDC3B expression vector without a splice site and restriction enzyme site. We showed that circFNDC3B increased migration and invasion in gastric cancer (GC). Ectopic expression of circFNDC3B reduced the level of E‐cadherin protein to promote the epithelial–mesenchymal transition in GC. RNA immunoprecipitation assays and RNA pull‐down assays confirmed that circFNC3B increased CD44 expression, which was associated with cell adhesion, via the formation of a ternary complex of circFNDC3B‐IGF2BP3‐ CD44 mRNA. These results indicated that circFNDC3B was associated with the degree of malignancy to highlight the specific characteristics of cell invasion. Abstract : We found that circFNDC3B played the role of a mediator between IGF2BP3 and CD44 mRNA via the formation of a ternary complex, which then promoted IGF2BP3 to promote CD44 levels, eventually leading to cell migration and invasion in GC.